Cost-Effectiveness Analysis of Atezolizumab Versus Chemotherapy as First-Line Treatment for Metastatic Non-Small-Cell Lung Cancer With Different PD-L1 Expression Status - Liu, Guoqiang; Kang, Shuo; Wang, Xinchen; Shang, Fangjian (Frontiers in Oncology, 2021)
ABSTRACT Background: Atezolizumab could significantly improve clinical outcomes and was associated with less toxicity compared with chemotherapy as the first-line treatment of PD-L1-selected patients with EGFR and ALK wild-type metastatic non-small-cell lung cancer (NSCLC). However, the economic outcomes remain unclear yet in China. This study aimed to investigate the cost-effectiveness of atezolizumab versus chemotherapy as first-line therapy for metastatic NSCLC with different PD-L1 expression status from the Chinese health sector perspective. Methods: A decision-analytic model was conducted to evaluate the economic outcomes for the first-line treatment of EGFR and ALK wild-type metastatic NSCLC with atezolizumab and chemotherapy in high PD-L1 expression, high or intermediate PD-L1 expression and any PD-L1 expression populations, respectively. The efficacy and safety data were obtained from the IMpower110 trial. Cost and utility values were gathered from the local charges and published literatures. Incremental cost-effectiveness ratio (ICER) was estimated. A scenario analysis for a patient assistance program (PAP) was conducted. One-way and probabilistic sensitivity analyses were performed to explore the robustness of the model results. Results: Atezolizumab yielded additional 0.91 QALYs, 0.57 QALYs, 0.42 QALYs in comparison with chemotherapy, and the ICERs were $123,778.60/QALY, $142,827.19/QALY, $168,902.66/QALY in the high PD-L1 expression, high or intermediate PD-L1 expression, and any PD-L1 expression populations, respectively. When PAP was available, the ICERs were $52,414.63/QALY, $52,329.73/QALY, $61,189.66/QALY in the three categories of PD-L1 expression status populations, respectively. The ICERs were highly exceed the willingness-to-pay (WTP) threshold of $30,828/QALY (three times of per capita gross domestic product of China in 2019) in China. One-way sensitivity analyses suggested that the cost of atezolizumab played a vital role in the model outcomes, and the probabilistic sensitivity analyses showed atezolizumab had 0% probability of being was unlikely to be cost-effective at the WTP threshold regardless of PD-L1 expression status and whether the PAP was available or not. Conclusions: Atezolizumab as first-line treatment for PD-L1-selected metastatic NSCLC patients without EGFR mutations or ALK translocations is unlikely to be cost-effective compared with chemotherapy regardless of PD-L1 expression status in the Chinese context.